Radiological and Clinical Features and Outcomes of Patients with Primary Pulmonary Salivary Gland-Type Tumors - Xiaoyu Han; Jianchu Zhang; Jun Fan; Yukun Cao; Jin Gu; Heshui Shi (Canadian Respiratory Journal)
Aim. To analyze the radiological, clinical, and prognostic features of primary pulmonary salivary gland-type tumors (SGTs) and improve their diagnosis. Materials and Methods. We retrospectively collected clinical and pathological data for 32 SGT cases confirmed by pathology and analyzed their radiological features, clinical presentations, and treatment outcomes. Results. Mucoepidermoid carcinoma (MEC) was more likely to occur in younger patients than was adenoid cystic carcinoma (ACC) (35 ± 15 years vs 48 ± 16 years, p=0.038). MEC was equally distributed between both sexes, whereas ACC was more frequent in females (66.7%). The main presenting symptom of SGT was cough (56.3%), followed by dyspnea (40.6%), associated with the tumor location. ACC more frequently involved the trachea or main bronchus (86.7% vs 25.0%, p=0.001) and more commonly presented as lobulated or circumferential thickening than MEC (93.3% vs 37.5%, p=0.002). MEC more frequently presented as obvious enhancement than ACC (68.8% vs 31.3%, p=0.001). CT findings suggestive of airway obstructive disease were more likely to be observed with MEC than ACC (73.3% vs 25.0%; p=0.021). The SUVmax in 8 of 10 patients with PET/CT data exceeded 2.2 but was less than 6.0. The overall survival (OS) at 3 and 5 years was 90.9% and 72.2% in all patients, respectively. Tumor-node-metastasis (TNM) stage, surgery, and patient age were associated with OS (p≤0.001, p=0.001, and p=0.001, respectively). Conclusion. SGTs commonly occur in patients at a young age and are associated with weak invasive features and a good prognosis. The predominant site and CT characteristics are significantly different between ACC and MEC.